Political capacity and corruption nexus: Re-examining evidence for developing countries - Saranjam Baig; Cuneyt Yenigun; Khalid Mehmood Alam (Economies, 2022)
This article examines the question of whether developing countries with strong political capacity have lower levels of corruption. Despite the ubiquity of literature on corruption, the relationship between a state's political capacity and corruption has not been addressed by the existing academic literature. To measure the political capacity of a country, the authors have used relative political capacity (RPC), an indicator that gauges the effectiveness of governance by its ability to meet or exceed their expected extractive capabilities and its ability to implement a set of policy choices. On the one hand, politically capable and stable governments are in a position to pursue their political and economic goals, such as reducing corruption. On the other hand, a strong political capacity provides them with the opportunity for rent-seeking and corruption. This implies that a state's strong political capacity can be either a 'boon' or 'bane' to implement a set of desired policy goals. Based on this assertion, the authors test the hypothesis of whether a strong relative political capacity increases or reduces the level of corruption. The analysis uses the ordinary least-squares and two-stage least squares methods for 98 developing countries to test the hypothesis. The findings suggest that the explanatory power of political capacity is at least as important as conventionally accepted causes of corruption, such as economic development, and democracy.
Keywords: 330; corruption; developing countries; institutions; relative political capacity; state's capacity